Product Market Deregulation and Employment Outcomes: Evidence from the German Retail Sector - Charlotte Senftleben-König (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper investigates the effects of the deregulation of shop-opening hours legislation on retail employment in Germany. In 2006, the legislative competence was shifted from the federal to the state level, leading to a gradual deregulation of shop opening restrictions in most of Germany s sixteen federal states. The paper exploits regional variation in the legislation in order to identify the effect of product market deregulation on retail employment. We find robust evidence that the deregulation had negative effects on retail employment, with considerable heterogeneity in terms of the type of employment as well as establishment size. Employment losses are most pronounced for small retail stores and are almost exclusively borne by full-time employees.
Keywords: J21; L51; L81; 330